2021
DOI: 10.1186/s12913-021-06712-w
|View full text |Cite
|
Sign up to set email alerts
|

Trends in treatment for patients with depression in general practice in Norway, 2009–2015: nationwide registry-based cohort study (The Norwegian GP-DEP Study)

Abstract: Background Depression is highly prevalent, but knowledge is scarce as to whether increased public awareness and strengthened government focus on mental health have changed how general practitioners (GPs) help their depressed patients. This study aimed to examine national time trends in GP depression care and whether trends varied regarding patient gender, age, and comorbidity. Methods Nationwide registry-based cohort study, Norway. The study popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
1
15
1
Order By: Relevance
“…According to a Norwegian study from 2019 and an Australian study from 2017 [ 25 , 35 ] on patient-reported depression treatment in general practice, many depressed patients prefer other forms of treatment than antidepressants. Our study supports these findings, and another Norwegian study found that the proportion of patients receiving antidepressant treatment decreased in the period 2009–2015 [ 8 ]. However, our study also suggests that one of the reasons patients do not want antidepressants is that they do not want such treatment in the absence of follow-up.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to a Norwegian study from 2019 and an Australian study from 2017 [ 25 , 35 ] on patient-reported depression treatment in general practice, many depressed patients prefer other forms of treatment than antidepressants. Our study supports these findings, and another Norwegian study found that the proportion of patients receiving antidepressant treatment decreased in the period 2009–2015 [ 8 ]. However, our study also suggests that one of the reasons patients do not want antidepressants is that they do not want such treatment in the absence of follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…According to earlier international studies more than 90% of patients consulting for depression were treated by GPs alone [ 7 ]. Today, 20% of patients with a new diagnosis of depression in Norway are referred to specialised care [ 8 ]. In addition, an increasing proportion of patients probably seeks help from private therapists or from community-based low-threshold services, although there is no official statistics on the extent to which these services are being used.…”
Section: Introductionmentioning
confidence: 99%
“…Long GP-patient relationship (9–14 years) was more common among patients 40 years and older, while short GP-patient relationship (1–2 years) was more common among those younger than 40 years. It has been documented that referral rates to specialist health care among older patients in Norway and the UK were lower than for younger patients [ 24 , 25 ]. Our analysis was adjusted for patients’ age, we also performed stratified analyzes by age, which gave similar estimates in both strata.…”
Section: Discussionmentioning
confidence: 99%
“…For each prescription of an antidepressant drug, NorPD provided information on date of dispensing and generic drug information (Anatomical Therapeutic Chemical (ATC) code). Data sources and variables have been described previously [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most antidepressants are prescribed by GPs [ 2 , 3 ], but the prescribing levels vary considerably between countries [ 4 8 ]. Recent studies indicate trends towards less drug treatment in the Netherlands, UK, and Norway [ 7 , 9 , 10 ], while treatment rates remained stable in the US [ 8 ]. The number of GP contacts for depression increased in the Netherlands [ 4 , 9 ] but was unchanged in Norway [ 10 ].…”
Section: Introductionmentioning
confidence: 99%